Cost of cardiovascular diseases in the United Kingdom. Issue 10 (15th May 2006) - Luengo-Fernández, R; Leal, J; Gray, A; Petersen, S; Rayner, M
Abstract : Objective: To estimate the economic burden of cardiovascular disease (CVD) in the United Kingdom, including health and non-healthcare costs, and the proportion of total CVD cost due to coronary heart disease (CHD) and cerebrovascular disease. Design and setting: Prevalence-based approach to assess CVD-related costs from a societal perspective. Patients: All UK residents in 2004 with CVD ( International classification of diseases, 10th revision (ICD-10) codes I00–I99) and subgroups with CHD (ICD-10 codes I20–I25) or cerebrovascular disease (ICD-10 codes I60–I69). Main outcome measures: Healthcare costs were estimated from expenditure on community health and social services, accident and emergency care, hospital care, rehabilitation and drugs. Non-healthcare costs were estimated from data on informal care and from productivity losses arising from morbidity and premature death. Results: CVD cost the UK economy £29.1 billion in 2004, with CHD and cerebrovascular disease accounting for 29% (£8.5 billion) and 27% (£8.0 billion) of the total, respectively. The major cost component of CVD was health care, which accounted for 60% of the cost, followed by productivity losses due to mortality and morbidity, accounting for 23%, with the remaining 17% due to informal care-related costs. Conclusions: CVD is a leading public health problem in the UK measured by the economic burden of disease. This study identified the size and main components of that burden, and will help to inform decisions about research priorities and to monitor the impact of policy initiatives.